Martin J. Sherwin collection relating to J. Robert Oppenheimer - Sherwin, Martin J.
Research material gathered by Sherman, Kai Bird, Alice Kimball Smith, and others regarding J. Robert Oppenheimer. Used by Bird and Sherman in writing American Prometheus: The Triumph and Tragedy of J. Robert Oppenheimer (2005). Includes correspondence, interviews, oral histories, government records, topical files, printed matter, photographs, and other papers. Documents Oppenheimer's work as director of the Los Alamos Scientific Laboratory, his political views, and investigations of his Communist associations. Subjects include the atomic bomb, hydrogen bomb, international control of atomic energy and weaponry, national security, and the U.S. Atomic Energy Commission. Persons represented include Hans A. Bethe, Haakon Chevalier, Lee A. DuBridge, Francis Fergusson, Leslie R. Groves, Paul Horgan, George F. Kennan, David Eli Lilienthal, Frank Oppenheimer, Katherine P. Oppenheimer, Lewis L. Strauss, Jean Tatlock, and Edward Teller.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Author, biographer, and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bethe, Hans A. -- 1906-2005.; Bird, Kai; Chevalier, Haakon, -- 1902-1985.; DuBridge, Lee A. -- 1901-1994.; Fergusson, Francis; Groves, Leslie R., -- 1896-1970.; Horgan, Paul, -- 1903-1995.; Kennan, George F. -- 1904-2005.; Lilienthal, David Eli, -- 1899-1981.; Oppenheimer, Frank, -- 1912-1985.; Oppenheimer, J. Robert, -- 1904-1967.; Oppenheimer, Katherine P. -- 1910?-1972.; Smith, Alice Kimball; Strauss, Lewis L; Tatlock, Jean; Teller, Edward, -- 1908-2003.; Los Alamos Scientific Laboratory; U.S. Atomic Energy Commission; Atomic bomb; Atomic bomb -- Moral and ethical aspects; Communism -- United States; Hydrogen bomb; Hydrogen bomb -- Moral and ethical aspects; Internal security -- United States; National security -- United States; Nuclear arms control -- International cooperation; Nuclear energy -- International cooperation; Nuclear physics -- United States; Nuclear weapons; Science -- Moral and ethical aspects -- United States; Science -- Political aspects -- United States; United States -- Politics and government -- 20th century; Authors; Biographers; Educators